(1237) Multi-objective linear programming البرمجة الخطية متعددة الأهداف - Hamza, Abdel-Kader (The Institute Of National Planning., 2018)
This paper attempts to apply of mathematical programming to the analysis of economic problems and the elaboration of algorithm and programms for solving economic models. such models provide us with analysis of national development which depends on, and interacts with, national economic conditions.